2013
DOI: 10.1371/journal.pone.0052972
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified α-Amylase Inhibitor Peas Are Not Specifically Allergenic in Mice

Abstract: Weevils can devastate food legumes in developing countries, but genetically modified peas (Pisum sativum), chickpeas and cowpeas expressing the gene for alpha-amylase inhibitor-1 (αAI) from the common bean (Phaseolus vulgaris) are completely protected from weevil destruction. αAI is seed-specific, accumulated at high levels and undergoes post-translational modification as it traverses the seed endomembrane system. This modification was thought to be responsible for the reported allergenicity in mice of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
(25 reference statements)
1
21
1
Order By: Relevance
“…Prescott et al found that GM alpha-amylase inhibitor (AAI) peas had an adjuvant effect on non-cross-reactive OVA responses. However, in a more comprehensive study, we demonstrated the absence of an adjuvant effect also using AAI peas in the same experimental model reported herein [22]. Additionally, we found that a cross-reactive allergic response against pea lectin and AAI developed upon AAI and nGM pea consumption.…”
Section: Discussionsupporting
confidence: 78%
“…Prescott et al found that GM alpha-amylase inhibitor (AAI) peas had an adjuvant effect on non-cross-reactive OVA responses. However, in a more comprehensive study, we demonstrated the absence of an adjuvant effect also using AAI peas in the same experimental model reported herein [22]. Additionally, we found that a cross-reactive allergic response against pea lectin and AAI developed upon AAI and nGM pea consumption.…”
Section: Discussionsupporting
confidence: 78%
“…While uncommon, some adverse effects have been occasionally detected in transgenic lines such as the unexpected immune reaction in mice consuming peas expressing the α-amylase 1 inhibitor (Prescott et al, 2005) although this early finding has not been confirmed in a more extensive study (Lee et al, 2013b).…”
Section: G Genetic Transformationmentioning
confidence: 99%
“…In several food allergy models, including ours, some of the immunized animals even appear to be non- or low responders, i.e., responding with no or weak anaphylaxis after allergen challenge and/or weaker allergen-specific IgE and IgG1 production than the rest of the group [25-29]. Further, food allergy responses have been reported to vary between labs [30] and the same strain of mice from different mouse providers [31] (and unpublished observations). Microbiota variations may contribute to these inter-individual and inter-lab variations in food allergy responses in mice, yet there is limited knowledge on how the microbiota influence food allergy models.…”
Section: Introductionmentioning
confidence: 99%